Aspects of Legal Change and Social Change - Nugroho, Ageng; Setiawan, Ahmad Fahrudi; Adriyanto, Adriyanto; Mutaqin, A. Imam Al (East Asian Journal of Multidisciplinary Research, 2025)
Social life requires law as a tool to create harmony, resolve conflicts, and control social behavior. Law also acts as a social engineering tool that can direct societal change towards a better, fairer, and more prosperous life. However, law often faces challenges in responding to dynamic social changes due to developments in technology, economy, and social structure. This study aims to analyze the relationship between law and social change and the aspects that influence legal change. By using normative legal research methods, the results of the study show that legal change and social change are closely related. Law must be responsive to demands for change in society in order to remain relevant in carrying out its function as a social controller and a tool for change.